The Effect of Disclosure of Other Comprehensive Income, Profitability, Leverage, and Company Size on Earnings Management (Study on Financing Institutions Sub-Sector Service Companies Listed on the Indonesia Stock Exchange for the 2018-2019 Period) - Erfan Effendi; Masnur Masnur; Rike Rahmadanti (Enrichment : Journal of Management, 2021)
The purpose of this study is to determine whether or not the disclosure of other comprehensive income, profitability, leverage, and company size has an effect on earnings management in the service companies sub-sector of financial institutions listed on the Indonesia Stock Exchange for the 2018-2019 fiscal year. This study makes use of secondary data from financial reports provided by the Indonesian Stock Exchange (IDX) on its website, www.IDX.co.id. The population for this study is a 19-company service firm subsector of financial institutions listed on the Indonesian Stock Exchange. Purposive sampling was used to collect data. Multiple linear regression analysis is the analytical technique used. Income disclosure had no influence on earnings management, profitability had no effect on earnings management, leverage had no effect on earnings management, and company size had no effect on earnings management. However, other factors like as total revenue, profitability, leverage, and fit size all have an effect on earnings management.